27.12 MHz Radiofrequency Ablation for Benign Cutaneous Lesions. (5th April 2016) - Kim, Dong Hyun; Hyun, Dong Ju; Piquette, Raymonde; Beaumont, Clément; Germain, Lucie; Larouche, Danielle
Abstract : As surgical and/or ablative modalities, radiofrequency (RF) has been known to produce good clinical outcomes in dermatology. Recently, 27.12 MHz RF has been introduced and has several advantages over conventional 4 or 6 MHz in terms of the precise ablation and lesser pain perception. We aimed to evaluate the clinical efficacy and safety of 27.12 MHz RF for the treatment of benign cutaneous lesions. Twenty female patient subjects were enrolled. Digital photography and a USB microscope camera were used to monitor the clinical results before one session of treatment with 27.12 MHz RF and after 1 and 3 weeks. Treated lesions included telangiectasias, cherry and spider angiomas, skin tags, seborrheic keratoses, lentigo, milium, dilated pore, acne, piercing hole, and one case of neurofibroma. For vascular lesions, clinical results were excellent for 33.3%, good for 44.4%, moderate for 11.1%, and poor for 11.1%. For nonvascular lesions (epidermal lesions and other benign cutaneous lesions), clinical results were excellent for 48.3%, good for 45.2%, moderate for 3.2%, and poor for 3.2%. No serious adverse events were observed. Mild adverse events reported were slight erythema, scale, and crust. The 27.12 MHz RF treatment of benign vascular and nonvascular lesions appears safe and effective after 3 weeks of follow-up.